Morphometry of blood monocytes in malignant lymphoma - Sokol, R J; Hudson, G; Wales, J; James, N T (Journal of clinical pathology, 1985)
Morphometric methods were used to study the ultrastructure of blood monocytes in 23 patients with Hodgkin's disease, 12 patients with non-Hodgkin's lymphoma, and 20 normal subjects. The results were analysed using both univariate and multivariate methods. Both analyses supported the interpretation that the total mitochondrial contribution to the cellular ultrastructure was less in Hodgkin's disease than in the other two groups, with smaller mitochondrial volume fractions, volumes, and surface areas being found. In the patients with non-Hodgkin's lymphoma univariate analysis suggested that monocyte nuclei were larger, with more euchromatin and a relatively smaller heterochromatin-euchromatin interface; the cell profile area was larger and the surface to volume ratio was smaller compared with normal subjects. Morphological changes have not previously been described in blood monocytes in malignant lymphoma, but they may be the counterpart of the known mononuclear phagocyte dysfunction.